Enjoyment in language teaching: A study into EFL teachers' subjectivities - Thumvichit A. (2023)
Although teacher enjoyment has been positively related to teacher well-being and performance, little is known about the combination of perspectives and experiences that contribute to it. This study uses Q methodology to identify, characterise and compare divergent viewpoints of tertiary-level English as a Foreign Language (EFL) teachers regarding enjoyment within their professional context. A Q sort of 44 statements reflecting enjoyment in foreign language teachers was administered to 40 participants. By-person factor analysis was conducted to identify common patterns across the Q sorts. Three viewpoints emerged, namely classroom engagement, career value and social interaction. The narratives show that the unique composites of experiences within these viewpoints characterise enjoyment for each group of EFL teachers. To boost or recover their enjoyment, EFL teachers are advised to clearly communicate their expectations for student behaviour, use positive reinforcement when teaching, seek opportunities for professional growth, establish career goals and embrace opportunities for collaboration.